2010
DOI: 10.3201/eid1611.100777
|View full text |Cite
|
Sign up to set email alerts
|

Measles Virus Strain Diversity, Nigeria and Democratic Republic of the Congo

Abstract: Differences in epidemiologic patterns are only partially explained by vaccination practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…It has been reported that measles vaccination may not prevent the development of symptoms with wild type measles virus, but studies have shown that vaccination protects children, especially those in endemic regions, from severe measles infection, thereby reducing the chances of measles-related deaths (8,(17)(18)(19)(20). Although studies have reported low protective antibodies in the target population after vaccination in Nigeria, these reports may not give the true picture of immune memory and readiness after reinfection, since only HA antibodies were measured (4,24).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that measles vaccination may not prevent the development of symptoms with wild type measles virus, but studies have shown that vaccination protects children, especially those in endemic regions, from severe measles infection, thereby reducing the chances of measles-related deaths (8,(17)(18)(19)(20). Although studies have reported low protective antibodies in the target population after vaccination in Nigeria, these reports may not give the true picture of immune memory and readiness after reinfection, since only HA antibodies were measured (4,24).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, two strains from Rostov-na-Donu (MVi/Rostov-na-Donu. RUS (B2KIN-A, B2KIN-B, and B2KIN-C) differing by up to 2 nt were detected (2). From 18 of these viruses, including three B2KIN-A, two B2KIN-B, and nine B2KIN-C strains collected between December 2004 and February 2006, the P and H genes were sequenced (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…International partners, including the GAVI-Alliance, are supportive of Congolese efforts. [1][2][3][4][5] Overall, the country is unlikely to achieve most of the Millennium Development Goals by 2015, without strong and sustained economic growth [6] The Human Development Index of the DRC equals 0.286, resulting in its ranking as 187th among the least developed countries (http:// hdrstats.undp.org/en/countries/profiles/COD.html). Annals of Tropical Medicine and Public Health | Jul-Aug 2013 | Vol 6 | Issue 4…”
Section: Introductionmentioning
confidence: 99%
“…[8,11,16,17] Of all the countries in Africa, the DRC and Nigeria are also reported to still have the highest average annual incidence and mortality associated with measles. [4,9,18] Since its inception in 1978 until 1990, the EPI in DRC, with the support of bilateral co-operation, managed to achieve significant progress in vaccination coverage for six vaccine-preventable diseases-tuberculosis, poliomyelitis, diphtheria, tetanus, pertussis, and measles. After the yellow fever vaccine was introduced in 2003, the DRC further expanded the spectrum of vaccines by introducing viral hepatitis B vaccine (2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation